ترقية كفاءة الطلاب للمحادثة بالعربية في الجامعة محمدية أتشيه: فرص وتحديات - Yusliani, Hamdi; Zikri, Awwaluz (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
This article talks about the topic of the importance of improving student qualifications at university level in terms of speaking skills in Arabic with the research location at the Muhammadiyah University of Aceh Campus in Banda Aceh in recent times. Speaking skills in Arabic for non-Arabic speakers are still considered the most difficult language skills to be applied, despite how easy and effortless the theory of Arabic speaking skills when taught by lecturers to students in the classroom. Among the problems that lecturers and students regularly face when practicing Arabic speaking skills is the fear of grammatical errors in Arabic (nahwu and sharaf) when speaking, as well as concerns about pronunciation errors. This article attempts to diagnose the various problems faced in the implementation of teaching Arabic speaking skills, in addition to trying to find opportunities and challenges that might be used to improve the level and ability of the Arabic language speaking among students at Muhammadiyah University in Aceh. This article is a qualitative one, by using descriptive analysis explaining the problems faced and finding solutions as the way out of the problem of implementing Arabic speaking skills among students at Muhammadiyah University of Aceh as an important finding and final conclusion of this article.